Selective expression of TSPAN2 in vascular smooth muscle is independently regulated by TGF‐β1/SMAD and myocardin/serum response factor. Issue 6 (3rd March 2017) - Zhao, Jinjing; Wu, Wen; Zhang, Wei; Wei Lu, Yao; Tou, Emiley; Ye, Jiemei; Gao, Ping; Jourd'heuil, David; Singer, Harold A.; Wu, Mingfu; Long, Xiaochun
ABSTRACT: Tetraspanins (TSPANs) comprise a large family of 4‐transmembrane domain proteins. The importance of TSPANs in vascular smooth muscle cells (VSMCs) is unexplored. Given that TGF‐β1 and myocardin (MYOCD) are potent activators for VSMC differentiation, we screened for TGF‐β1 and MYOCD/serum response factor (SRF)–regulated TSPANs in VSMC by using RNA‐seq analyses and RNA‐arrays. TSPAN2 was found to be the only TSPAN family gene induced by TGF‐β1 and MYOCD, and reduced by SRF deficiency in VSMCs. We also found that TSPAN2 is highly expressed in smooth muscle–enriched tissues and down‐regulated in in vitro models of VSMC phenotypic modulation. TSPAN2 expression is attenuated in mouse carotid arteries after ligation injury and in failed human arteriovenous fistula samples after occlusion by dedifferentiated neointimal VSMC. In vitro functional studies showed that TSPAN2 suppresses VSMC proliferation and migration. Luciferase reporter and chromatin immunoprecipitation assays demonstrated that TSPAN2 is regulated by 2 parallel pathways, MYOCD/SRF and TGF‐β1/SMAD, via distinct binding elements within the proximal promoter. Thus, we identified the first VSMC‐enriched and MYOCD/SRF and TGF‐β1/SMAD‐dependent TSPAN family member, whose expression is intimately associated with VSMC differentiation and negatively correlated with vascular disease. Our results suggest that TSPAN2 may play important roles in vascular disease.—Zhao, J., Wu, W., Zhang, W., Lu, Y. W., Tou, E., Ye, J., Gao, P., Jourd'heuil, D., Singer, H. A., Wu, M., Long, X. Selective expression of TSPAN2 in vascular smooth muscle is independently regulated by TGF‐β1/SMAD and myocardin/serum response factor. FASEB J. 31, 2576–2591 (2017). www.fasebj.org